Evaluasi Kinerja Perangkat Desa Dalam Pengelolaan Website Desa (Studi Evaluasi Kinerja Perangkat Desa Banguntapan Kecamatan Banguntapan Kabupaten Bantul Dalam Pengelolaan Website Desa) - Veronika Lidia (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
The enactment of Law Number 6 of 2014 concering Villages, became the starting point for openness in the village, especially regarding village information. Villages are required to have a Village Information System or known as SID. This journal is written to look at several things. First, the management of the Banguntapan Village website. Second, the management of the Banguntapan Village website is not optimal. Third, the efforts made by the village government in improving the performance of village officials in managing the Banguntapan Village website. The research method used is qualitative descriptive method. The results of this study first show that this condition is due to the lack of human resources owned by the Banguntapan Village Government, which resulted in the process of forming the village website management team not being able to carry out. Second, the ability of the Banguntapan Villages apparatus in operating computer is still weak. The limited capabilities possessed by the Banguntapan Village apparatus result in the website management process. In addition to human resources another reason is the absence of supporting facilities such as special rooms, computers or laptops, as well as budgets for managing village website. Regarding human resources, the village government’s efforts are to provide technical guidance and training related to website management. In terms of supporting the management of village websites, the efforts made by the Banguntapan Village Government are only limited to preparing plans that will be included in the village budget. Keywords: Village Government, Village Apparatus, Performance, SID.